2007
DOI: 10.1183/09031936.00164706
|View full text |Cite
|
Sign up to set email alerts
|

Use of tunnelled catheters for malignant pleural effusions in patients fit for pleurodesis

Abstract: The aim of the present study was to examine the effectiveness of tunnelled pleural catheters (TPC) in patients with malignant pleural effusions who would otherwise be candidates for pleurodesis.Patients were selected from a previously reported database of 250 TPC insertions. The study group was selected based on lung re-expansion and survival as a surrogate maker of eligibility for pleurodesis procedure, as defined by survival of o90 days and lung re-expansion o80% postdrainage on a standard chest radiograph 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 25 publications
3
67
0
5
Order By: Relevance
“…TPC related pleurodesis has been reported to occur between 29 to 59 days post placement (72,77,78 (79). In a recent randomized trial, Impact of Aggressive versus Standard Drainage Regimen Using a Long-Term Indwelling Pleural Catheter trial (ASAP trial), rates of spontaneous pleurodesis were higher in patients daily drainage compared to the every other day drainage of pleural fluid via a TPC (47% vs. 24%, respectively; P = 0.003).…”
Section: Tunneled Pleural Catheter (Tpc)mentioning
confidence: 99%
“…TPC related pleurodesis has been reported to occur between 29 to 59 days post placement (72,77,78 (79). In a recent randomized trial, Impact of Aggressive versus Standard Drainage Regimen Using a Long-Term Indwelling Pleural Catheter trial (ASAP trial), rates of spontaneous pleurodesis were higher in patients daily drainage compared to the every other day drainage of pleural fluid via a TPC (47% vs. 24%, respectively; P = 0.003).…”
Section: Tunneled Pleural Catheter (Tpc)mentioning
confidence: 99%
“…15 Many centres use chemical sclerotherapy with percutaneous catheters as the first choice treatment option in MPE. 16,17 However, there has always been the problem that obstruction of the narrow diameter occurs easily. Kiliç et al recommended the use of Cystofix catheter because of the problem of obstruction in 8F catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that up to 20.6% (range, 1.6-20.6%) of IPCs need to be removed due to complications. [9][10][11]14,15,21,22 Nonetheless, serious complications are uncommon; the most common being pleural infection (0-16.7%). 23 The TIME2 study reported that the risk of pleural infection was 13.4% in the IPC group compared with 1.9% in the talc slurry pleurodesis group.…”
Section: Discussionmentioning
confidence: 99%